ANALISIS FAKTOR â FAKTOR YANG BERPENGARUH TERHADAP LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERUSHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Bella Arika Phonna, 12.05.52.0010; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2016)
This study aims to determine the effect of profitability (ROE), IndependentÂ Commissioner Board Size, Leverage, Size and institutional ownership, publicÂ ownership, and the liquidity of the disclosure of Corporate Social ResponsibilityÂ area companies including food and beverage categories listed in the Indonesia StockÂ Exchange.Â The population is all food and beverage company in the Indonesia StockÂ Exchange in 2010 - 2014. The sampling technique used was purposive sampling. TheÂ analytical tool used in this research is Multiple Regression AnalysisÂ Partial results of this study show the public ownership of significant positiveÂ effect on disclosure of CSR while variable profitability, independent board size,Â leverage size, Institutional ownership and liquidity does not affect the broadÂ disclosure of CSR.Keywords: Profitability, Comissioner Independent Size, Leverage Size, Institutional Ownership, Public Ownership, Liquidity, CSR DisclosureÂ